Cognitive Behavioural Therapy and Light Dark Therapy for Maternal Postpartum Insomnia Symptoms: Protocol of a Parallel-Group Randomised Controlled Efficacy Trial - Verma, Sumedha; Rajaratnam, Shantha M. W.; Davey, Margot; Wiley, Joshua F.; Bei, Bei (Frontiers in Global Women's Health, 2021)
Background: Symptoms of insomnia are common in new mothers and have been associated with a range of negative maternal and child outcomes. Despite this, interventions to improve maternal postpartum sleep remain scarce. Cognitive Behavioural Therapy (CBT) and Light Dark Therapy (LDT) represent two promising interventions for insomnia symptoms and associated daytime consequences such as fatigue. This randomised controlled trial examines whether CBT and LDT improve maternal insomnia symptoms as the primary outcome and maternal sleep disturbance, mood, fatigue, and sleepiness as secondary outcomes. This protocol paper outlines the development, design, and implementation of the trial. Methods: Participants are an Australian community-sample of 90 first-time mothers who are 4–12 months postpartum with self-reported symptoms of insomnia (Insomnia Severity Index scores ≥ 8). Exclusion criteria include current severe sleep/psychiatric disorders, unsettled infant sleep behaviour, sleep-affecting medication use, and photosensitivity. Eligible women are randomised into a CBT (strategies targeting sleep, worries, fatigue, and relaxation), LDT, or a treatment-as-usual control condition. Interventions are therapist-assisted and personalised through two telephone calls and include a series of automated intervention emails delivered over 6 weeks. Primary and secondary outcomes are assessed at four time points: baseline, intervention mid-point, post-intervention, and 1-month post-intervention. Discussion: If found effective, these interventions could represent efficacious, safe, and inexpensive treatments for improving postpartum insomnia and mitigate its negative impact on maternal well-being. Interventions tested are highly scalable and can be integrated into postpartum care and made available to the broader community. ANZCTR trial registration: Accessible at: https://anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12618000842268.